Stable Zn-Ion Hybrid Supercapacitor Zinc Anode Achieved by Artificial Protective Layer of Nitrogen-Sulfur Co-Doping Activated Carbon. Issue 2 (1st February 2023) - Yu, Juan; Jia, Xuefeng; Peng, Jiaxin; Wang, Tian; Feng, Hangshuo; Meng, Bicheng; Zhao, JunKai; Yang, Naixing
Abstract : Zinc metal anodes are one of the promising aqueous anodes due to their low redox potential and high capacity. However, the growth of dendrites severely destabilizes the electrode/electrolyte interface and accelerates the generation of side reactions that ultimately degrade the electrochemical performance. Here, we used a simple and effective interface engineering strategy to construct nitrogen and sulfur double-doped orange peel-based biomass activated carbon (NS-OPC) artificial protective layer on zinc foil. Among them, nitrogen-containing functional groups and S heteroatoms can regulate the transport and deposition of Zn 2+, and the hierarchical porous structure of activated carbon not only provides a large number of active sites for Zn 2+, but also provides enough space for the growth of Zn 2+ dendrites. The symmetric cell with NS-OPC artificial protective layer showed excellent cycle stability (1200 h) at the current density of 1 mA cm −2 . Finally, the YP50||NS-OPC/Zn full cell was constructed to validate the performance of the NS-OPC/Zn. The capacity retention rate was 92.6％ after 3000 cycles at 10 A g −1 .This work provides a feasible strategy for accelerating the industrial application of aqueous zinc-ion hybrid supercapacitors.